A Land Management Model Using Dantzig-Wolfe Decomposition - Nazareth, L. (Management Science, 1980)
This paper deals with a mathematical model designed to provide guidelines for managing a land resource over an extended period of time. We develop a framework which permits sequences of management decisions to be conveniently formulated, and their associated costs and benefits specified. This takes the form of a network. Each path in the network represents a possible decision sequence. We study how to select suitable decision sequences and what proportion of the resource to manage with each selected sequence, so as to optimize some specified objective and meet the constraints imposed on management of the resource. An L.P. model is formulated. The solution strategy decomposes the L.P. matrix using Dantzig-Wolfe decomposition and solves the subproblems efficiently by dynamic programming or a network flow algorithm. Computational aspects are discussed and the concepts and procedures are illustrated in the Appendix, for forest management.